(untitled) (Herald of the National Children’s Medical Center, 2025)
Necrotizing enterocolitis (NEC) is one of the most severe and frequently encountered gastrointestinal (GI) diseases in newborns and premature infants. The incidence is 1–5 per 1,000 live births, with 80–90% of cases occurring in premature infants and those with low birth weight (<2500 g). Surgical stages of NEC are observed in 20–40% of cases. The average mortality rate ranges from 30% to 40%, and in very low birth weight infants (<1000 g), it exceeds 80%. Studying the long-term outcomes of surgical treatment for NEC is of great importance for prognosis and improving the quality of life of affected patients.